The Mediating Role of Trust in Shaping Customer Loyalty of Bank: Insighths from a developing country perspective - Husne Jahan, Chowdhury; G. M. Azmal Ali, Quaosar; Nazifa Anbar, Saba; Md Abidur, Rahman (Financial Markets, Institutions and Risks)
This study seeks to analyze the complex interplay among such factors as trust, customer satisfaction, and service quality, which are known to affect customer loyalty. Another specific goal is to examine whether trust plays a mediating role in shaping customer loyalty across the banking domain. Drawing upon the relationship marketing theory, this article emphasizes the importance of building and maintaining long-term customer relationships. Within a unified research framework, customer-centric approaches were prioritized to foster loyalty and retention. Following the existing literature, this study utilizes a quantitative method. Interviewer-administered questionnaires were employed to collect survey data from 416 regular customers of the top 15 conventional and Islami Shariah-based commercial banks. The model validation was performed using the structural equation modeling method in Smart-PLS version 4.1.0.6. The findings of these results indicate that customer satisfaction and service quality have a favorable and direct impact on customer loyalty. Furthermore, it was discovered that the trust variable partially mediates the impact of customer satisfaction and service quality on customer loyalty. By focusing on a specific geographic region and industry, this study provides insights that are tailored to the nuances of the cultural, economic, and regulatory environment, thereby filling a gap in the literature on trust and loyalty in emerging market economies. The research findings enhance theoretical knowledge and managerial practices in the banking industry by addressing the value of trust as a mediator in fostering loyalty.